A fast handover protocol for 6LoWPAN wireless mobile sensor networks - Berguiga, Abdelwahed; Youssef, Habib (Telecommunication systems, 2018)
Wireless sensor networks (WSNs) are finding application in numerous fields. For many of these applications, some or all of the sensor nodes are mobile. Mobility management in WSNs is a challenging and has been the subject of intensive research. In this paper, we propose an IP-based mobility management protocol named Fast handover Proxy Mobile IPv6 for Sensor networks (FPMIPv6-S). FPMIPv6-S provides network-based mobility support for 6LoWPAN WSN when a sensor node moves between two Personal Area Networks. It is an improved version of the PMIPv6 protocol proposed for mobility management in IPv6 networks. FPMIPv6-S messages are carried by RPL protocol. Analytical evaluation of the proposed protocol shows significantly improved performance with respect to network mobility cost (signalling traffic) when compared to PMIPv6 and RPL alone. We also integrated the FPMIPv6-S protocol in the NS-3 simulator and performed a thorough performance comparison of FPMIPv6-S and RPL.